Social Network Group Kube Mekar Sari Kelurahan Guntung, Bontang City: Jaringan Sosial Kelompok Kube Mekar Sari Kelurahan Guntung, Kota Bontang - Damayanti, Putri; Nanang, Martinus (Progress In Social Development, 2020)
ABSTRACT: KUBE is one of the programs launched by the Bontang city government in poverty reduction. KUBE in Bontang City was first formed in 2013. Based on data from the Bontang City Social Service in 2018, the number of KUBE in Bontang City reached 282 groups. The large number of KUBE can be a big hope for the local government in improving the welfare of the community. However, the implementation of the KUBE program in the city of Bontang has not met the government's expectations. This is made clear by the large number of KUBE in the city of Bontang that are not developing or moving towards independence. However, in the city of Bontang there is one KUBE that stands out the most, namely Mekar Sari. KUBE Mekar Sari is the best group at city, provincial to national levels. This study aims to determine how the process behind the success of KUBE Mekar Sari in achieving independence and the success of KUBE Mekar Sari can be seen from two sides, namely social and economic, and there are several factors that KUBE independence has a network of connections with each other. ABSTRAK: KUBE merupakan salah satu program yang dicanangkan oleh pemerintah kota Bontang dalam hal penanggulangan kemiskinan. KUBE di kota Bontang pertama kali dibentuk pada tahun 2013. Berdasarkan data Dinas Sosial kota Bontang pada tahun 2018, jumlah KUBE di kota Bontang mencapai 282 kelompok. Kuantitas KUBE yang tergolong banyak dapat menjadi harapan besar bagi pemerintah setempat dalam meningkatkan kesejahteraan masyarakat. Akan tetapi implementasi program KUBE di kota Bontang belum sesuai dengan harapan pemerintah. Hal tersebut diperjelas dengan banyaknya jumlah KUBE di kota Bontang yang tidak berkembang atau bergerak menuju kemandirian. Meskipun demikian, di kota Bontang terdapat satu KUBE yang paling menonjol dibanding dengan yang lainnya yaitu Mekar Sari. KUBE Mekar Sari adalah kelompok terbaik tingkat kota, provinsi hingga nasional. Penelitian ini bertujuan untuk mengetahui bagaimana proses di balik keberhasilan KUBE Mekar Sari dalam mencapai kemandirian dan keberhasilan KUBE Mekar Sari dapat dilihat dari dua sisi yaitu sosial dan ekonomi, dan ada beberapa faktor kemandirian KUBE memilki jaringan koneksi satu sama lain.